2014
DOI: 10.29252/jmj.12.2.25
|View full text |Cite
|
Sign up to set email alerts
|

Correct or incorrect use of inhalers in patients with dyspnea

Abstract: Introduction: One of the medications used by patients with dyspnea and asthma is sprays whose the way of application is very important. If these medications are not used properly, they will not be effective. The purpose of this study was to investigate the correct or incorrect use of sprays by patients. Material and Method: This double-blind observational analytical study was conducted on patients attending clinics in Jahrom from 2009 to 2013 selected by convenience sampling method. After obtaining patient's c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…These findings are in accordance with the findings of Fadaei et al, (2016) who found that approximately all of their subjects were trained in this regard but didn't follow these training [36]. These findings were explained by Restrepo et al, (2008) who reported that retention of instructions about appropriate use of inhaler is lost over time [37].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…These findings are in accordance with the findings of Fadaei et al, (2016) who found that approximately all of their subjects were trained in this regard but didn't follow these training [36]. These findings were explained by Restrepo et al, (2008) who reported that retention of instructions about appropriate use of inhaler is lost over time [37].…”
Section: Discussionsupporting
confidence: 82%
“…These results are supported by National asthma council (2008) which stated that large body of evidence from randomized trials have shown that patient's inhaler technique can be improved by education [17]. Also Fadaei et al, (2014) revealed that using inhaler correctly requires the patients to be informed about proper use instructions [36].…”
Section: Discussionsupporting
confidence: 54%
“… 16 Unfortunately, studies that focus on the evaluation of the inhalation technique are scars in Iran and most of them did not include patients with COPD. 17 , 18 , 19 …”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] Studies showed that 4–94% of patients with respiratory diseases use inhalers incorrectly. [ 4 ],[ 5 ],[ 6 ],[ 7 ] In addition, it has been shown that only 15–69% of healthcare providers (including physicians and nurses) can demonstrate correct inhaler use[ 8 ] and only 14.2% of physicians had an adequate knowledge of inhalation therapy. [ 9 ] Incorrect inhaler use not only results in ineffective symptom management[ 7 ] but also wastes $7–15 billion each year.…”
Section: Introductionmentioning
confidence: 99%